2019
DOI: 10.3390/s19245445
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study for Estimating the Cardiopulmonary Signals of Diverse Exotic Animals Using a Digital Camera

Abstract: Monitoring the cardiopulmonary signal of animals is a challenge for veterinarians in conditions when contact with a conscious animal is inconvenient, difficult, damaging, distressing or dangerous to personnel or the animal subject. In this pilot study, we demonstrate a computer vision-based system and use examples of exotic, untamed species to demonstrate this means to extract the cardiopulmonary signal. Subject animals included the following species: Giant panda (Ailuropoda melanoleuca), African lions (Panthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…The latter is specifically of great importance because it can contribute to easily disseminate the findings of this novel field in the zoo setting. However, the employment of more technology field-specific journals is still limited (i.e., we found only one publication in the journal Sensors [ 37 ]), likely due to the fact that these journals are more focused on recent advances in agriculture, livestock farming, and land sustainability where the application of automated monitoring systems is clearly greater. Thus, we suggest that a more interdisciplinary approach with regard to the choice of the most suitable journal is needed for zoo research on automated monitoring systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is specifically of great importance because it can contribute to easily disseminate the findings of this novel field in the zoo setting. However, the employment of more technology field-specific journals is still limited (i.e., we found only one publication in the journal Sensors [ 37 ]), likely due to the fact that these journals are more focused on recent advances in agriculture, livestock farming, and land sustainability where the application of automated monitoring systems is clearly greater. Thus, we suggest that a more interdisciplinary approach with regard to the choice of the most suitable journal is needed for zoo research on automated monitoring systems.…”
Section: Discussionmentioning
confidence: 99%
“…Although technology can integrate the current approaches applied in zoos for animal welfare monitoring and assessment, scientists are still far from taking full advantage of it [ 35 ]. For instance, when collecting physiological indicators of welfare such as heart and breathing rate or body temperature, the use of devices such as digital [ 37 ] and IR thermal cameras [ 39 ] or mobile ECG monitors programmed with algorithms [ 46 ] had the advantage that animals did not need to be anesthetized nor to carry over equipment which can be stressful and invasive procedures. A study on gorillas also suggested that IR thermal cameras may have the potential to investigate the emotional response of the animals; however, the authors stated that the application of this device in the absence of other related physiological/behavioural measures needs further validation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical and mathematical models can be used to evaluate the performance of the model. Al-Naji et al (2019) used machine vision to calculate the respiration rate of exotic animals (like Giant panda, African lions, Sumatran tiger, Koala, Red kangaroo, Alpaca, little blue penguin, Sumatran orangutan and Hamadryas baboon). The videos were recorded using a digital camera (Nikon D610, Nikon Inc., Tokyo, Japan) when the animals were not moving much to avoid any noise in the data.…”
Section: Machine Vision Technologymentioning
confidence: 99%
“…Once the symptoms of disease become evident, the producers either take no action, seek help from veterinary professionals, use antibiotics or adopt a combination of these three approaches to cure their livestock (Neethirajan, 2020). Getting to this point though involves understanding the physiological issues and novel sensing technology approaches have been investigated to estimate respiratory rates or detect behavioral changes linked to respiratory diseases to identify sick livestock at an early stage (Silva et al, 2008;Weixing and Zhilei, 2010;Mutlu et al, 2018;Al-Naji et al, 2019;Barbosa and Pereira, 2019;Lowe et al, 2019;Wu et al, 2020). Respiratory rate detection technology can be broadly classified into either contact or non-contact technologies.…”
mentioning
confidence: 99%
“…Therefore, the effective denoising of acquired WMSN images has been a hot topic in related fields [4][5][6]. Wavelet transform can characterize both time and frequency domain features, and effectively determine the abnormal points in the images and their degree of abnormality, due to these advantages, it has been widely applied in the field of image denoising [7][8][9][10][11]. Among the many wavelet denoising methods, the wavelet threshold denoising method is the most commonly-used method [12].…”
Section: Introductionmentioning
confidence: 99%